Nomogram for predicting survival in patients with unresectable and/or metastatic urothelial cancer who are treated with cisplatin‐based chemotherapy. Issue 16 (29th May 2013) - Galsky, Matthew D.; Moshier, Erin; Krege, Susan; Lin, Chia‐Chi; Hahn, Noah; Ecke, Thorsten; Sonpavde, Guru; Godbold, James; Oh, William K.; Bamias, Aristotle
<x xml:space="preserve">Abstract</x> BACKGROUND The current study was conducted to develop a pretreatment prognostic model for patients with unresectable and/or metastatic urothelial cancer who were treated with first‐line, cisplatin‐based chemotherapy. METHODS Individual data were pooled from 399 patients who were enrolled on 8 phase 2 and 3 trials evaluating cisplatin‐based, first‐line chemotherapy in patients with metastatic urothelial carcinoma. Variables selected for inclusion in the model were combined in a Cox proportional hazards model to produce a points‐based nomogram with which to predict the median, 1‐year, 2‐year, and 5‐year survival. The nomogram was validated externally using data from a randomized trial of the combination of methotrexate, vinblastine, doxorubicin plus cisplatin versus docetaxel plus cisplatin. RESULTS The median survival of the development cohort was 13.8 months (95% confidence interval, 12.1 months‐16.0 months); 68.2% of the patients had died at the time of last follow‐up. On multivariable analysis, the number of visceral metastatic sites, Eastern Cooperative Oncology Group performance status, and leukocyte count were each found to be associated with overall survival (P < .05), whereas the site of the primary tumor and the presence of lymph node metastases were not. All 5 variables were included in the nomogram. When subjected to internal validation, the nomogram achieved a bootstrap‐corrected concordance index of 0.626. When applied to the external validation cohort, the nomogram achieved a concordance index of 0.634. Calibration plots suggested that the nomogram was well calibrated for all predictions. CONCLUSIONS Based on routinely measured pretreatment variables, a nomogram was constructed that predicts survival in patients with unresectable and/or metastatic urothelial cancer who are treated with cisplatin‐based chemotherapy. This model may be useful in patient counseling and clinical trial design. Cancer 2013;119:3012—3019. © 2013 American Cancer Society.